"You Still Have to Try It!": Helping Picky Eaters in Classroom Groups. (December 2019) - Freeman, Stephanny F. N.; Hayashida, Kristen; Paparella, Tanya; Azad, Gazi; Flowers, Cyndi D.; Glamore, Allease
Many teachers struggle with implementing self-help eating goals for children with autism spectrum disorder (ASD). No group programs exist to target this important problem. We used findings from applied behavior analysis research and adapted single-subject interventions into a group-based eating program. In describing the program using two vignettes, children in two preschool special education classrooms are introduced to a character called "Esther the Eater" and then taught to expand their eating choices. The program is designed to be routine, fun, and classroom-friendly to help children with ASD try new foods.